THE EFFECT OF CLIMATE ON DEVELOPMENT VARIABILTAS Water-borne diseases - Sudarso Sudarso (Universitas Wijaya Kusuma Surabaya, 2009)
Global warming issue in 21 century this become especial issue. The effect of global warming besides at another phenomenon, like floods, erosion, dryness, increasing temperature of earth, climate change and also its influence to human being, especially for health. Climate change is expected to have considerablke impact on health, and one of the most important is waterborne diseases. Weather influences the transport and dissemination of the microbial agents via rainfall and runoff and survival and/or growth such factors as temperature. Knowledge about transport processes and fate of microbial pollutants associated with rainfall and snowmelt is key to predicting risk from change in weather variability. Water-borne diseases can be infected by many routes of exposure, as well as individual or population susceptibility, to waterborne pathogens, with water quality, avaibility, sanitation, and hygiene all playing a role.More than 100 types of pathogenic bacteria, viruses, and prozoa can be found in contaminated water.